A case of premature aging with recurrent pancreatitis and lipodystrophy - Dutta, Mita; Tabassum, Maliha; Islam, Mohammad Aminul; Hossain, Kazi Nazmul; Afsana, Faria; Amin, Mohammod Feroz; Pathan, Md Faruque; Pathan, Md Faruque (BIRDEM Medical Journal, 2023)
Werner’s syndrome (WS) is characterized by insulin resistance along with signs of premature aging. It poses great diagnostic challenge because of its unusual presentation. We describe a case of WS in a 30-year-old female, who presented with recurrent pancreatitis and documented hypertriglyceridemia along with hyperglycemia despite getting more than 200 units of insulin per day, without any history of hyperglycemic emergency such as diabetic ketoacidosis (DKA)/ hyperglycemic hyperosmolar state (HHS). Examination showed signs of premature aging (alopecia, progressive sharpening of facial features, loss of upper incisor teeth, wrinkles and freckles) and generalized wasting. Scalp biopsy confirmed the diagnosis. BIRDEM Med J 2023; 13(1): 56-59